Adhesion Formation and Intraperitoneal Catheters - Şadi Yılmaz; Davut Güven; Yurdanur Süllü; Özgür Erdoğan; İsmail Kılıco; İdris Koçak; Cazip Üstün (Medical Network, 2008)
OBJECTIVE: Aim of the present study was to determine effect of silicone and polyvinyl chloride in a rat model. STUDY DESIGN: A randomised blind study was performed using a rat model of laparotomy. Setting: Surgical Research laboratory in a university medical school. İntervention(s): Fifty four rats were divided into three groups:Group 1 (n:18),simple laparotomy; and group 2 (n:18) polyvinyl chloride were placed intraperitoneally;Group 3 (n:18),silicone was placed intraperitoneally. Main outcome measure(s): Three weeks after laparotomy,repeat laparotomy was performed and the adhesions were scored. RESULT General adhesion scores in groups 2 and 3 were higher than in group 1 (p<0.05). İn group 1, none of the rats presented adhesion.The results for groups 2 and 3 were similar. CONCLUSIONS: The overall adhesions score did not differed significantly between groups 2,3.Silicone and polyvinyl chloride causes adhesion development in rat model.